The Moon’s Early Magmatic Activities: From the Perspective of Lunar Alkali-Suite and Mg-Suite Samples - Wei Du; Jing Yang (Space: Science & Technology)
This review places emphasis on ancient lunar nonmare igneous samples alkali-suite and Mg-suite. The material on mineralogy and petrology of the Mg-suite presented here draws from “Lunar samples” by Papike et al. and “Origin of the lunar highlands Mg-suite: An integrated petrology, geochemistry, chronology, and remote sensing perspective” by Shearer et al. Readers can refer to these comprehensive studies for more information. The in-depth studies on Chang'e-5 (CE-5) lunar basaltic samples put new constraints on the thermal state of lunar interior, although the discussions on their formation mechanism heavily rely on the lunar magma ocean (LMO) models. Yet, chemical composition and structure of the lunar mantle are modified by migration of lunar materials during or after LMO fractionation. Alkali-suite rocks and Mg-suites are two important ancient lunar sample suites that represent early lunar magmatic activities. Studies on these samples are crucial to inverse modeling the pattern and scale of material migration inside the Moon during the “post-LMO” period. However, some Mg-suite samples and granitic samples are found outside the Procellarum KREEP (K, REE [rare earth element], and P) Terrane, bringing difficulties to explain their chemical characteristics and formation mechanisms. More work is needed to constrain the primitive melt formed deeply inside the Moon based on the updated LMO models, and to quantify the scale and effect of lunar mantle overturn. In addition, analysis on more lunar samples and lunar exploration missions with emphasis on ancient samples will also help to constrain their formation mechanisms, to refine the LMO differentiation models, and to depict the constitution of the lunar interior.